Case report: A case of severe acute hepatitis of unknown origin - Zhou, Yu-Jiao; Gu, Hui-Ying; Tang, Qi-Qin; Li, Fan; Zhu, Jin; Ai, Ting; Zhu, Kun; Xu, Bin-Yue; Wang, Qing; Huang, Ai-Long; Chen, Juan; Zhang, Zhen-Zhen (Frontiers in Pediatrics, 2022)
According to analyze etiology, clinical features, diagnostic methods, and treatment strategies by summarizing a suspected unexplained acute hepatitis case recently experienced, we are aiming to provide some information to enrich the clinical experience in diagnosis and treatment of severe acute hepatitis of unknown etiology in young children. A boy, aged 10 years and 6 months old, was admitted to the hospital due to acute abdominal pain, jaundice and exceptionally high levels of ALT and AST. A range of measures including patient history, physical examination, and routine laboratory testing, were performed. Furthermore, strategies such as Trio-based next generation sequencing (Trio-NGS) and liver biopsy, as well as metagenomic NGS (mNGS) of blood and liver samples were also performed. In summary, this case was an acute severe non-A-E hepatitis, who was considered as a probable case with hepatitis of unknown origin according the definition of the WHO. Trio-NGS of this case was negative. Evidences of Epstein-Barr virus (EBV), cytomegalovirus (CMV), herpes simplex viruses (HSV) infection were not found. Additionally, examinations related to adenovirus and SARS-CoV-2 were negative as well. However, torque teno virus (TTV) sequences was detected by mNGS of whole blood and liver tissue. As for treatment strategies, in addition to general treatment, this patient also underwent plasmapheresis and methylprednisolone treatment due to disease deterioration.The patient’s liver function was improved afterwards and discharged after one month treatment. Taken together, this work reported the clinical feature and treatment of severe acute hepatitis with Non A—E hepatitis in detail. The potential mechanism of liver damage might due to immune injury.